The Role of Glypican-3 in Regulating Wnt, YAP, and Hedgehog in Liver Cancer - Kolluri, Aarti; Ho, Mitchell (Frontiers in Oncology, 2019)
Glypican-3 (GPC3) is a cell-surface glycoprotein consisting of heparan sulfate glycosaminoglycan chains and an inner protein core. It has important functions in cellular signaling including cell growth, embryogenesis, and differentiation. GPC3 has been linked to hepatocellular carcinoma and a few other cancers, however, the mechanistic role of GPC3 in cancer development remains elusive. Recent breakthroughs including the structural modeling of GPC3 and GPC3–Wnt complexes represent important steps toward deciphering the molecular mechanism of action for GPC3 and how it may regulate cancer signaling and tumor growth. A full understanding of the molecular basis of GPC3-mediated signaling requires elucidation of the dynamics of partner receptors, transducer complexes, and downstream players. Herein, we summarize current insights into the role of GPC3 in regulating cancer development through Wnt and other signaling pathways, including YAP and hedgehog cascades. We also highlight the growing body of work which underlies deciphering how GPC3 is a key player in liver oncogenesis.